RETRACTED: Development of an algorithm for the operation of railway station infrastructure in unconventional situations - Parshin P.K.; Sergeeva T.G. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001